2014
DOI: 10.1097/mej.0b013e32835ed752
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a standard operating procedure on prehospital emergency care of patients presenting with symptoms of the acute coronary syndrome

Abstract: To determine whether a standard operating procedure (SOP) for prehospital management of patients with the acute coronary syndrome (ACS) improves the quality of patient care in terms of adherence to treatment guidelines of the European Society of Cardiology. Among a total of 1025 patient medical records collected from a period before and after the introduction of the SOP, 269 records included the working diagnosis of ACS and were then reviewed for guideline adherence. Most aspects of patient evaluation, monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 5 publications
4
8
1
1
Order By: Relevance
“…Our result is in agreement with those reported by Martinon et al [ 8 ] from Paris who found that the prevalence of automated ventilator use following RSI on paediatric TBI patients rose to 88% after the implementation of their guideline. Our result compares favourably to those found by Bosse et al [ 5 ] and Francis et al [ 6 ] from the physician-staffed EMS in Berlin. They investigated the impact of introducing SOPs for the pre-hospital treatment of acute exacerbation in COPD [ 5 ] and acute coronary syndrome (ACS) [ 6 ] and neither of the SOPs in these studies improved overall patient care.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our result is in agreement with those reported by Martinon et al [ 8 ] from Paris who found that the prevalence of automated ventilator use following RSI on paediatric TBI patients rose to 88% after the implementation of their guideline. Our result compares favourably to those found by Bosse et al [ 5 ] and Francis et al [ 6 ] from the physician-staffed EMS in Berlin. They investigated the impact of introducing SOPs for the pre-hospital treatment of acute exacerbation in COPD [ 5 ] and acute coronary syndrome (ACS) [ 6 ] and neither of the SOPs in these studies improved overall patient care.…”
Section: Discussionsupporting
confidence: 87%
“…Our result compares favourably to those found by Bosse et al [ 5 ] and Francis et al [ 6 ] from the physician-staffed EMS in Berlin. They investigated the impact of introducing SOPs for the pre-hospital treatment of acute exacerbation in COPD [ 5 ] and acute coronary syndrome (ACS) [ 6 ] and neither of the SOPs in these studies improved overall patient care. The authors introduced the SOPs by arranging staff meetings and distributing the SOP by e-mail and in paper copies.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Data demonstrate that there is little difference in analgesic effect within the dosing ranges most likely used in most EDs (from 0.1 to 0.15 mg/kg IV) [180]. Other studies have also found that obese patients do not require extra morphine and that, indeed, weight-based dosing is not truly necessary [173,181]. The "standard" initial dose of morphine of 0.1 mg/kg (about 7 mg in an adult) has been found to provide inadequate analgesia (i.e., less than 50% decrease in pain) in 2/3rds of ED patients [182].…”
Section: Morphinementioning
confidence: 86%
“…The drug has been around for as long as any other opioid and has excellent safety and efficacy when used appropriately. Despite theoretical and practical concerns about histamine release and hypotension, the use of morphine (including higher-risk patients such as cardiac and trauma cases) has not been associated with dangerous hypotension even in the relatively less controlled setting of prehospital care [173][174][175][176]. Some of the more interesting recent investigations of morphine in the acute care setting suggest that it may be combined with ketamine for increased efficacy (with minimization of hemodynamic risks) [143].…”
Section: Morphinementioning
confidence: 99%